The Effect Of Implementation Of Permenkes No 46 Of 2015 Regarding Accreditation Of Puskesmas, Primary Clinics, Places Of Mandiri Doctor Practices, And Mandiri Medical Practices On The Performance Of Human Resources And The Effectiveness Of Using The Use O - Ade Anggraini (Science Midwifery, 2022)
Effect of implementation of Permenkes no. 46 of 2015 concerning the accreditation of Health Centre, pratama clinics, independent doctor's practice, and independent dentist’s practice on the performance of human resources and the effectiveness of the use of funds and their impact on the quality of services at health centre. This study aims to determine whether there is an influence on the implementation of Permenkes no. 46 of 2015 concerning the accreditation of health centre, pratama clinics, independent doctor's practice, and independent dentist’s practice on the performance of human resources and the effectiveness of the use of funds and their impact on the quality of services at health centre in bekasi. This research was conducted based on purposive sampling, the aim of which was targeted at respondents of the head of health centre, administrative coordinator, treasurer Jaminan Kesehatan Nasional, treasurer bantuan operasional Kesehatan, treasurer Anggaran Pendapatan Belanja Daerah, so that sample of 100 respondents was obtained sufficiently and represented the population in the city of Bekasi. This study used a research questionnaire that was distributed to 20 health centre units. The method used is SEMPLS (partial least square structural equation modeling) which is based on an evaluation of the interdependence relationship between variables. From the results of the study it was found that there was a significant positive strong relationship between the implementation of Permenkes no. 46 of 2015 concerning the accreditation of health centre, pratama clinics, independent doctor's practice, and independent dentist’s practice on human resource performance. There was no significant relationship between the implementation of Permenkes no. 46 of 2015 concerning the accreditation of health centre, pratama clinics, independent doctor's practice, and independent dentist’s practice to the effectiveness of the use of funds shows a significant positive relationship between Permenkes no. 46 of 2015 concerning the accreditation of health centre, pratama clinics, independent doctor's practice places, and independent dentist’s practice places on the quality of services at healt centre in Kota Bekasi. Permenkes no. 46 of 2015 on the performance of human resources and the effectiveness of the use of funds and their impact on the quality of services at the puskesmas.